2018
DOI: 10.1039/c7lc01114h
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spheroid clearing on a microfluidic chip

Abstract: Spheroids are three-dimensional (3D) cell cultures that aim to bridge the gap between the use of whole animals and cellular monolayers. Microfluidics is regarded as an enabling technology to actively control the chemical environment of 3D cell cultures. Although a wide variety of platforms have been developed to handle spheroid cultures, the development of analytical systems for spheroids remains a major challenge. In this study, we engineered a microfluidic large-scale integration (mLSI) chip platform for tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Recently developed tissue clearing methods have been used to produce high quality images [ 25 ], but most of the commercially available protocols last about 72 h and are extremely expensive. Some studies attempted to adapt tissue clearing procedures for spheroid and organoid protocols [ 17 , 18 , 19 , 20 ], however, these studies used light sheet microscopy and not a standard confocal microscope, and they required long procedures or use of specific designated microchips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently developed tissue clearing methods have been used to produce high quality images [ 25 ], but most of the commercially available protocols last about 72 h and are extremely expensive. Some studies attempted to adapt tissue clearing procedures for spheroid and organoid protocols [ 17 , 18 , 19 , 20 ], however, these studies used light sheet microscopy and not a standard confocal microscope, and they required long procedures or use of specific designated microchips.…”
Section: Discussionmentioning
confidence: 99%
“…We, as well as others, have shown that spheroids can deposit dense ECM and thus be used ex vivo as a model for the pancreatic tumor [ 13 , 14 , 15 , 16 ]. Previous attempts to adapt optic clearing protocols for spheroids and organoids typically required either the use of light sheet microscopes, special flow chip devices, physical sectioning, or long procedures [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose, the clearing solutions promote the homogenization of the refractive index (RI) through the spheroids and reduce the light scattering effect [ 15 , 23 ]. In the literature, several optical clearing methods have been used for improving the spheroids analysis, namely Clear T [ 19 ], Clear T2 [ 18 , 20 , 21 ], SeeDB [ 14 , 18 ], FocusClear ™ [ 22 ], BABB [ 24 , 25 , 26 , 27 ], Scale [ 14 , 18 ], CUBIC [ 28 ], and CLARITY [ 29 , 30 ]. Among these, Clear T and Clear T2 methods are organic-solvent and detergent free, the solutions are easy to handle, and the protocols are not very time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…The PACT and PARS methods use lower concentrations of fixatives and hydrogel monomers in conjugation with higher SDS concentrations (8% (w/v)), to facilitate and increase the passive diffusion of SDS into the sample and thus obtain a greater clearing without using the electrophoresis system. Furthermore, the authors also investigated the influence of the pH value in the media surrounding the hydrogel-embedded spheroids on the swelling and shrinkage of the gel(Silva Santisteban et al, 2018). In the PACT method, sample-hydrogel hybrid is simply merged with an SDS solution, while in the PARS method the removal of the lipids is performed by perfusing continually the sample with the SDS solution(Yang et al, 2014b).CLARITY-based methods were also used to clear spheroids.…”
mentioning
confidence: 99%
“…The results demonstrated that the clearing time of the spheroids off-chip took 10-14 days, while this process was reduced to 2 days when a microfluidic system was used. Furthermore, the authors also investigated the influence of the pH value in the media surrounding the hydrogel-embedded spheroids on the swelling and shrinkage of the gel(Silva Santisteban et al, 2018). These changes lead to the creation of osmotic pressure and thus facilitate the lipids extraction from the spheroids.…”
mentioning
confidence: 99%